Plays for Christmas (Bell & Hyman Ltd, 1984)
Four plays about Christmas: A Child is Born by Christine Chaundler, No Such Thing as Christmas by Andrew McCann, King George and the Turkish Knight and The Third Wish by Ricky Owen.
Keywords: Juvenile literature-Drama-Christmas